Trends and Research Focus of the Jigsaw Learning Model in Economic Learning: Bibliometric Review and Analysis - Fadli Agus Triansyah; Suwatno Suwatno; Amir Machmud (Universitas Pendidikan Indonesia, 2023)
Cooperative learning is a learning model that demands more student interaction working together in groups to improve student academic achievement. One of the cooperative learning models is the jigsaw learning model, which is a learning model that directs students to communicate with each other by giving assignments so that students have a responsibility to their peers. This study aims to determine trends and research focus on the publication of the jigsaw learning model in economics learning which then obtains the distribution for 2004 - 2022. Data collection techniques are done by downloading files on the dimensions database to see trends in publications with the largest number of documents, classification of institution rankings or universities, countries, journals, and documents, and the use of shared keywords. The method used is bibliometric analysis. A total of 46 documents collected through the dimensions database were then put together in 1 file in csv format and entered into the VOSviewer application to get network visualization and overlay visualization. The study results show that the trend of publications related to the jigsaw learning model in economics studies has increased yearly. The documents with the highest number are in the